Characteristics of cryoprotectors used for long-term storage of donor dendritic cells - Timohina, Oksana V.; Hancharou, Andrei Y. (Experimental Biology and Biotechnology, 2021)
Monocyte-derived donor dendritic cells are promising for use in the treatment of cancer. However, there are some problems that currently limit their clinical use. One of which is the cryopreservation of cells followed by restoration on demand. А cryoprotector must be added to the nutrient medium in order to reduce or completely eliminate the damaging factors acting on cells during freezing. Cryoprotectors refer to a wide range of sugars, diols and amino acids that stabilise biomolecules in various ways, depending on their molecular weight and mechanism of action on cells. The work describes groups of cryoprotectors (endo- and exocellular, mixed and combined cryoprotectors), as well as presents techniques of cryopreservation of dendritic cells.